Carcinosarcoma of the ovary. Issue 1 (1st January 2008) - Silasi, D.-A.; Illuzzi, J. L.; Kelly, M. G.; Rutherford, T. J.; Mor, G.; Azodi, M.; Schwartz, P. E.
Abstract : The objective of this study was to evaluate the treatment and outcome in patients with ovarian carcinosarcoma. The Tumor Board Registry was reviewed for patients with ovarian carcinosarcoma treated at our institution from June 1993 to December 2004. The medical records were retrospectively analyzed with emphasis on cytoreduction, cytotoxic regimens, progression-free interval, and survival. Twenty-two patients were identified. All but two presented with advanced stage disease. The median survival for the entire cohort was 38 months. Median survival was 46 months for 18 optimally debulked (<1 cm) patients and 27 months for four suboptimally debulked (>1 cm) patients. Six patients were treated with optimal cytoreduction and adjuvant cisplatin (40 mg/m 2 × 1 day) and ifosfamide (1200 mg/m 2 /day × 4 days) every 28 days. Median progression-free interval in the cisplatin and ifosfamide group was 13 months, and median survival was 51 months. The combination of carboplatin (AUC 5) and taxol (175 mg/m 2 ) every 21 days was administered to four patients as first-line chemotherapy following optimal cytoreduction. In the carboplatin and taxol group, median progression-free interval was 6 months and median survival was 38 months. The difference in survival between the cisplatin and ifosfamide group and the carboplatin and taxol group was not statistically significant ( P = 0.48). In conclusion, patients with ovarian carcinosarcoma usually present with advanced stage disease. Treatment consists of optimal cytoreduction and chemotherapy. The most effective cytotoxic regimen remains to be determined. First-line cisplatin and ifosfamide or carboplatin and taxol can achieve survival rates observed in epithelial ovarian cancer.